What we 'see' when we read: Visualization and vividness in reading fictional narratives. (August 2018) - Brosch, Renate
Abstract: Visualization is defined as the production of mental images in the process of reading (Esrock 2005: 633). This article is concerned with varieties of visualization during an absorbing reading of a fictional narrative, the mental images that range from an indistinct and largely automatic default visualization to the much more vivid images that occur at significant stages in the narrative. Neuroscientific studies of vision have collected a large and impressively varied body of experimental evidence for two major processing streams – the dorsal and the ventral-specialized for vision-for-action and vision for-perception respectively. Further experiments distinguish different dispositional specializations: visualizers with a high spatial visualizing ability demonstrating a more efficient use of resources in the dorsal pathway, and those with a high object visualization and more efficient use of the ventral pathway (Kozhevnikov et al., 2010: 29). We can assume that both types of mental processing will be prompted in fictional narratives with differences in prominence depending on their authors' inclinations and the design and purpose of the narrative text. According to AmedeoD'Angiulli (2013 : 7), who conducted elaborate tests of vividness in mental imagery using written descriptive passages as stimulus, dynamic imagery was significantly less vivid than static imagery. These results confirm traditional literary criticism based on introspection which argues that detailed description of static objects elicits an especially lively imagination. However, narratives can provoke even stronger visualizations by rendering subjective moments of seeing in which a fictional character is emotionally involved. In encouraging readers to shift now and then from the default mode of motion-oriented visualizing to a more affective and more conscious object visualization, literary fictions exercise their power to evoke imaginings that one would not generate by oneself. This may indicate that literary narratives can prove a training ground for expanding one's visualizing capacities.